Traumatic Paraplegia: Spine is not always the Right Answer - Mrichi, Salma; Oudrhiri, Mohamed Yassaad; Boutarbouch, Mahjouba; Melhaoui, Adyl; Arkha, Yasser; Elouahabi, Abdessamad (RA Journal of Applied Research, 2022)
Paraplegia is rarely reported as a consequence of isolated blunt head trauma. We report a case of a 28-years old patient admitted to our department after a traumatic brain injury. On admission he presented a paraparesis without sensory disturbance in both legs. Spine CT (Computed Tomography) scan and MRI (Magnetic Resonance Imaging) scan of the spine were both normal. Brain CT scan and MRI showed bilateral precentral gyri contusion. Early rehabilitation was key to quick motor recovery. Our case highlights traumatic brain injury as a differential diagnosis of paraplegia.